PENGARUH LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MODERASI - Felicia, Felicia; Viriany, Viriany (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study was to examine the effect of liquidity (CR) and firm size (SIZE) on profitability with capital structure as a moderating variable. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The sample of this study includes 86 companies selected through purposive sampling technique. The results of the study indicate that liquidity has a negative and significant effect on profitability and firm size has no effect on profitability, while capital structure is not able to moderate the effect of liquidity and firm size on profitability.